EFEKTIVITAS PELAKSANAAN ADMINISTRASI DAN SUPERVISI DALAM MENDUKUNG PROGRAM SEKOLAH MERDEKA BELAJAR - Muhammad Amien Rais; M Choirul Muzaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the implementation of educational administration and supervision in supporting the implementation of the Merdeka Curriculum at SD Negeri 1 Trimulyo Mataram, Seputih Mataram District. The approach used is qualitative with a case study type. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation, while data analysis used thematic analysis. The results showed that education administration in this school is orderly, adaptive and supports the flexibility of learning. Supervision is collaborative, educative and data-based, which improves teachers' competence in implementing differentiated and project-based learning. The synergy between administration and supervision creates a conducive and transformative school ecosystem, in line with the spirit of Merdeka Belajar. This finding confirms that the successful implementation of the Merdeka Curriculum is highly dependent on effective school governance and reflective and sustainable supervision.